Hubungan Sikap dan Keterampilan Dengan Kepatuhan Perawat Dalam Hand Hygiene Five Moment Di Rumah Sakit Bhayangkara Balikpapan - Fhirawati Fhirawati; Yoga Kurniawan (Yayasan Jompa Research and Development, 2023)
Nurse Compliance in Hand Hygiene Five Moments at Bhayangkara Balikpapan Hospital: A Correlation of Attitudes and Skills Nurses practice hand hygiene to lessen the frequency of nosocomial infections in hospitals. When it comes to reducing nosocomial infections, hand cleanliness has a significant impact on both the health of nurses and patients. The study's goal was to ascertain how attitudes, abilities, and nurse compliance in five-moment hand hygiene at Balikpapan's Bhayangkara Hospital related to one another. With a cross sectional approach, this research method employs a quantitative analytic descriptive design. 121 nurses from the Bhayangkara Hospital in Balikpapan participated in the sample. The Chi Square test is employed. The findings demonstrated that the majority of the respondents had a good outlook, were competent, and also followed the five-moment hand hygiene rule. Then, a p-value test found a relationship between attitude and hand hygiene compliance with a 0.05, and a 0.00, 0.05, p-value test found a relationship between skills and hand hygiene compliance. Nurse compliance with the five-minute hand hygiene process will be influenced by the attitude and abilities of the nurses. According to the study's findings, nurses should have a better understanding of the significance of hand hygiene for protecting patients and themselves from infection since compliance will be higher if accompanied by a cheerful attitude about this hand hygiene.